2014
DOI: 10.1242/dev.095430
|View full text |Cite
|
Sign up to set email alerts
|

Development of five digits is controlled by a bipartite long-range cis-regulator

Abstract: Conservation within intergenic DNA often highlights regulatory elements that control gene expression from a long range. How conservation within a single element relates to regulatory information and how internal composition relates to function is unknown. Here, we examine the structural features of the highly conserved ZRS (also called MFCS1) cis-regulator responsible for the spatiotemporal control of Shh in the limb bud. By systematically dissecting the ZRS, both in transgenic assays and within in the endogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 43 publications
(70 reference statements)
5
73
1
3
Order By: Relevance
“…These results establish the Ets1 and Ets2 genes as bona fide HAND2 target genes in early limb buds. As the ETS binding sites in the ZRS are essential for Shh expression in the posterior limb bud (Lettice et al, 2014; Lettice et al, 2012), HAND2-mediated up-regulation of the Ets transcription factors likely helps to reinforce Shh expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results establish the Ets1 and Ets2 genes as bona fide HAND2 target genes in early limb buds. As the ETS binding sites in the ZRS are essential for Shh expression in the posterior limb bud (Lettice et al, 2014; Lettice et al, 2012), HAND2-mediated up-regulation of the Ets transcription factors likely helps to reinforce Shh expression.…”
Section: Resultsmentioning
confidence: 99%
“…Localized Shh expression depends on the interaction of different transcriptional regulators with the ZRS. In particular, the interaction with HOX, PBX, ETS and HAND2 transcriptional complexes has been implicated in activation of Shh in the limb bud, while TWIST1, ETV and GATA factors prevent anterior ectopic expression (Capellini et al, 2006; Galli et al, 2010; Kmita et al, 2005; Kozhemyakina et al, 2014; Lettice et al, 2014; Lettice et al, 2012; Mao et al, 2009; Zhang et al, 2010; Zhang et al, 2009). How the ZRS integrates these various inputs over time is unknown, but the resulting posterior restriction of SHH signaling is essential for proliferative expansion and anterior-posterior (AP) patterning of the distal limb bud mesenchyme that will form the skeletal elements of the zeugopod and autopod (Ahn and Joyner, 2004; Chiang et al, 2001; Harfe et al, 2004; Zhu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…3C analysis revealed that Shh activation by the ZRS correlates with physical contacts between them (54), suggesting a looping of the chromatin path between the enhancer and Shh. A study that combined genetic manipulation of the enhancer locus, transgenics, and 3D-FISH showed that while the 5= end of the ϳ800-bp ZRS is sufficient to drive an adjacent reporter gene, the 3= end of the enhancer is required for long-range regulation and full expression of Shh in the developing forelimbs and hind limbs and, consequently, complete digit sets (199). The Shh locus was further observed by 3D-FISH to loop out of its chromosome territory when the gene is active (54).…”
Section: Chromatin Looping and Looping Outmentioning
confidence: 99%
“…Interestingly, the Shh remote limb enhancer comprises a region required for long-but not short-range activation of gene expression [134], suggesting that different factors bound to an enhancer may be involved in its activity and its ability to maintain interactions.…”
Section: From Enhancer Modules To Structural/regulatory Ensemblesmentioning
confidence: 99%